Opportunities and challenges associated with fecal progesterone metabolite analysis - Peter, Innocent Damudu; Haron, Abd Wahid; Abdullah, Faez Firdaus Jesse; Ajat, Mokrish; Mark Hiew, Wen Han; Wan Jaffar, Wan Nor Fitri; Yahaya, Muhammad Sanusi; M. Alamaary, Mohammed Saad (Veterinary World, 2018)
Conventionally, plasma or milk progesterone evaluations are used to determine the reproductive status of female animals. Collection of such samples is often associated with difficulties of animal handling and restraint. Measurable quantities of progesterone metabolites are found in feces of animals. Their concentrations are known to be well correlated to plasma progesterone levels and are, therefore, used as non-invasive samples for assessing reproductive function in a wide range of animal species. Although the analysis of fecal progesterone metabolites has been widely accepted in many laboratories, several factors are known to affect the results from this valuable analytical technique. Some of these factors include storage/transportation media for fecal samples, type of solvent that is used for extraction of progesterone metabolites from feces, and the type and sensitivity of an assaying technique employed. Although fecal progesterone metabolites analysis is associated with some difficulties, it can effectively be used to monitor reproductive function in a wide range of animal species. This review aims to highlight the usefulness of fecal progesterone metabolite analysis as a non-invasive technique in monitoring reproductive function in animals. The article mainly focuses on the many opportunities and challenges associated with this analytical technique.